Immigration Law: Analysis Of The Application Of Criminal Law Towards Immigration Permit Abuse In Bima NTB - Wardin, Wardin; Syamsuddin, Syamsuddin; Ihlas, Ihlas (Law and Justice, 2025)
The misuse of immigration permits constitutes a form of legal violation that has the potential to disrupt public order, national security stability, and undermine the integrity of a country’s immigration system. This study aims to comprehensively analyze the application of criminal law to the practice of immigration permit misuse, whether committed by foreign nationals or domestic actors. The main focus of this research is to examine the effectiveness of criminal law norms in the Immigration Law and their implementation in practice, including both juridical and non-juridical obstacles faced by law enforcement officers. The research method used is a normative juridical method with statutory and conceptual approaches, accompanied by case studies from several relevant court decisions. Data were obtained through literature study and analyzed qualitatively. This research finds a disparity between the legal norms that have been regulated and their implementation in the field. Law enforcement is often hindered by weak inter-agency coordination, limited human resources, and the suboptimal legal instruments in providing a deterrent effect. These findings indicate the importance of reformulating clearer criminal norms as well as strengthening the capacity of immigration institutions and law enforcement officers. The novelty of this study lies in the integrative approach between immigration law and criminal law, which have often been applied sectorally. This research is expected to contribute scientifically to the improvement of immigration policy and the enhancement of the effectiveness of criminal law enforcement against immigration violations in Indonesia. Penyalahgunaan izin keimigrasian merupakan pelanggaran hukum yang berpotensi mengganggu ketertiban umum, mengancam keamanan nasional, dan merusak integritas sistem keimigrasian suatu negara. Penelitian ini bertujuan untuk menganalisis secara komprehensif penerapan hukum pidana terkait penyalahgunaan izin keimigrasian di Bima, Nusa Tenggara Barat (NTB), yang melibatkan baik warga negara asing maupun pelaku dalam negeri. Fokus utama penelitian ini adalah mengkaji efektivitas norma hukum pidana dalam Undang-Undang Keimigrasian Indonesia beserta implementasinya di tataran praktis, termasuk hambatan yuridis dan non-yuridis yang dihadapi oleh aparat penegak hukum di wilayah Bima. Penelitian ini menggunakan metode yuridis normatif melalui pendekatan perundang-undangan dan konseptual, serta didukung oleh studi kasus dari putusan pengadilan setempat yang relevan. Data dihimpun melalui studi kepustakaan yang komprehensif dan dianalisis secara kualitatif. Temuan penelitian mengungkapkan adanya kesenjangan yang signifikan antara norma hukum yang berlaku dan pelaksanaannya di lapangan. Penegakan hukum kerap terhambat oleh lemahnya koordinasi antarinstansi, keterbatasan sumber daya manusia, serta instrumen hukum yang belum optimal sehingga gagal memberikan efek jera yang memadai. Temuan ini menyoroti urgensi untuk merumuskan kembali norma pidana yang lebih jelas serta memperkuat kapasitas institusi keimigrasian maupun aparat penegak hukum. Kebaruan dari penelitian ini terletak pada pendekatan integratif antara hukum keimigrasian dan hukum pidana dalam konteks wilayah yang spesifik, guna menjawab persoalan regulasi yang selama ini sering kali diterapkan secara sektoral. Pada akhirnya, penelitian ini diharapkan dapat memberikan kontribusi ilmiah bagi perbaikan kebijakan keimigrasian serta meningkatkan efektivitas penegakan hukum pidana terhadap pelanggaran keimigrasian di Indonesia.